2014
DOI: 10.3892/mmr.2014.2174
|View full text |Cite
|
Sign up to set email alerts
|

Pingyangmycin stimulates apoptosis in human hemangioma-derived endothelial cells through activation of the p53 pathway

Abstract: Abstract. Pingyangmycin (also known as Bleomycin A5) is produced by Streptomyces verticillus var. pingyangensis n.sp., and has anti-tumor activities against a variety of tumor cells. The aim of the present study was to determine the molecular mechanism(s) underlying the therapeutic effects of pingyangmycin against infantile hemangiomas. Human hemangioma-derived endothelial cells (HemECs) were treated with pingyangmycin at varying concentrations (100, 200 or 300 µg/ml), and the morphological changes and apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…The effects of PYM on hemangioma-derived endothelial cells have been studied in vitro. PYM treatment (100-300 µg/ml) resulted in a significant and dose-dependent induction of apoptosis in human hemangioma-derived endothelial cells (HemECs) (24). These results were in line with the results of the present study, which showed that PYM inhibited the proliferation of EOMA cells in a dose-and time-dependent manner and significantly induced apoptosis at 100 µg/ml.…”
Section: A B Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The effects of PYM on hemangioma-derived endothelial cells have been studied in vitro. PYM treatment (100-300 µg/ml) resulted in a significant and dose-dependent induction of apoptosis in human hemangioma-derived endothelial cells (HemECs) (24). These results were in line with the results of the present study, which showed that PYM inhibited the proliferation of EOMA cells in a dose-and time-dependent manner and significantly induced apoptosis at 100 µg/ml.…”
Section: A B Discussionsupporting
confidence: 91%
“…Zhao et al (25) reported that patients with maxillofacial squamous cell carcinomas subjected to microwave-induced hyperthermia followed by intravenous injection of PYM, exhibited an increased number of apoptotic cancer cells; this effect was likely to be mediated via downregulation of Bcl-2 and upregulation of Bax. In HemECs, the induction of apoptosis was attributed to the activation of the p53 pathway (24). The present study demonstrated that the PI3K/Akt pathway has a significant role in PYM-induced inhibition of cell viability and invasive ability as well as induction of apoptosis in EOMA cells.…”
Section: A B Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Another novel finding of this study was that PUMA, a newly identified target of miR-143, mediated the expression of TJPs in endothelial cells. As an apoptosis inducer, PUMA has been shown to be involved in the apoptosis of endothelial cells 40 41 . In the current study, methamphetamine failed to affect the apoptosis of endothelial cells ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a large number of studies on the successful treatment of hemangioma with oral propranolol have been reported, making propranolol the first-line drug for the treatment of hemangioma (15)(16)(17). Pingyangmycin, as an antitumor antibiotic, forms thrombus in tumor blood sinus and causes fibrosis of the tumor body when injected into a tumor, which is a reliable and effective treatment method for children with hemangioma (18)(19)(20). With the rapid development of laser technology, it has been gradually applied to the treatment of clinical diseases.…”
Section: Discussionmentioning
confidence: 99%